Image‐based modeling of blood flow in cerebral aneurysms treated with intrasaccular flow diverting devices. (11th April 2019) - Mut, Fernando; Chung, Bong Jae; Chudyk, Jorge; Lylyk, Pedro; Kadirvel, Ramanathan; Kallmes, David F.; Cebral, Juan R.
Abstract: Modeling the flow dynamics in cerebral aneurysms after the implantation of intrasaccular devices is important for understanding the relationship between flow conditions created immediately posttreatment and the subsequent outcomes. This information, ideally available a priori based on computational modeling prior to implantation, is valuable to identify which aneurysms will occlude immediately and which aneurysms will likely remain patent and would benefit from a different procedure or device. In this report, a methodology for modeling the hemodynamics in intracranial aneurysms treated with intrasaccular flow diverting devices is described. This approach combines an image‐guided, virtual device deployment within patient‐specific vascular models with an immersed boundary method on adaptive unstructured grids. A partial mesh refinement strategy that reduces the number of mesh elements near the aneurysm dome where the flow conditions are largely stagnant was compared with the full refinement strategy that refines the mesh everywhere around the device wires. The results indicate that using the partial mesh refinement approach is adequate for analyzing the posttreatment hemodynamics, at a reduced computational cost. The results obtained on a series of four cerebral aneurysms treated with different intrasaccular devices were in good qualitative agreement with angiographic observations. Promising results were obtained relating posttreatment flow conditions and outcomes of treatments with intrasaccular devices, which need to be confirmed on larger series. Abstract : This paper describes a methodology for modeling the hemodynamics in intracranial aneurysms treated with intrasaccular flow diverting devices. This approach combines an image‐guided, virtual device deployment within patient‐specific vascular models with an immersed boundary method on adaptive unstructured grids. The results obtained on a series of four cerebral aneurysms treated with different intrasaccular devices were in good qualitative agreement with angiographic observations.